2007
DOI: 10.1088/0022-3727/40/8/s04
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silicon nanocrystals in silane plasmas for nanoelectronics and large area electronic devices

Abstract: The synthesis of silicon nanocrystals in standard radio-frequency glow discharge systems is studied with respect to two main objectives: (i) the production of devices based on quantum size effects associated with the small dimensions of silicon nanocrystals and (ii) the synthesis of polymorphous and polycrystalline silicon films in which silicon nanocrystals are the elementary building blocks. In particular we discuss results on the mechanisms of nanocrystal formation and their transport towards the substrate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 36 publications
0
56
0
1
Order By: Relevance
“…As a matter of fact increasing silane flow rate at relatively high total pressure moves the process from radical to nanocrystal growth, as we have reported in the past for pm-Si:H and μc-Si:H films [7,22]. Indeed, over the last decade, our group has focused on the study of dusty plasmas [23], particularly on the plasma synthesis of silicon clusters [5,7,8,22,24]. These clusters, generated in the plasma, can be either amorphous or crystalline, depending on the hydrogen dilution.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…As a matter of fact increasing silane flow rate at relatively high total pressure moves the process from radical to nanocrystal growth, as we have reported in the past for pm-Si:H and μc-Si:H films [7,22]. Indeed, over the last decade, our group has focused on the study of dusty plasmas [23], particularly on the plasma synthesis of silicon clusters [5,7,8,22,24]. These clusters, generated in the plasma, can be either amorphous or crystalline, depending on the hydrogen dilution.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, the extension of the PECVD processes from a-Si:H, pm-Si:H and μc-Si:H to epitaxial layers also brings new light to the interpretation of the growth process of these materials. Favoring the synthesis of silicon nanocrystals in the plasma has been our main driving force over the past 10 years and has resulted in the development of polymorphous silicon films where silicon nanocrystals and radicals contribute to the growth [5,7,8]. Moreover, we have shown that under conditions of μc-Si:H deposition from silicon nanocrystals, the nature of the substrate and plasma surface treatments prior to deposition play a key role on the growth process [6].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding the growth process at such low temperature, there is still a lot to be understood as well. It has been shown previously in our laboratory that in some process conditions, crystalline Si nanoparticles are generated in the gas phase [20]. These nanocrystals play an important role in the deposition and can be incorporated to the film resulting in polymorphous or microcrystalline silicon materials on glass substrates [21,22].…”
Section: Resultsmentioning
confidence: 95%
“…Powder is identified as a possible additive source for the deterioration of device performance 5,9 and precautions are often taken to reduce its formation. On the other hand, it has been shown that the formation of powder under certain conditions is beneficial to the deposition of a-Si:H and c-Si: H. 13,14 However, a systematic study of the effect of powder on the material quality of c-Si: H films, performed at a constant ion bombardment and a constant R d , is still lacking.…”
mentioning
confidence: 99%